Security for Microsoft Visual Basic .NET - Robinson, Ed 1967- (Microsoft Press, 2003)
This resource provides best practices, step-by-step code walk-throughs, and concise explanations of key security terms, issues, and jargon to help developers create and run secure code with Visual Basic.